Atomic scale characterization of carbon partitioning and transition carbide precipitation in a medium carbon steel during quenching and partitioning process. (2022) - Ghosh, Sumit; Rakha, Khushboo; Reza, Shahriar; Somani, Mahesh; Kömi, Jukka
Abstract: Transmission electron microscopy (TEM) and 3D Atom probe tomography (APT) were used to investigate the elemental partitioning, carbon (C) redistribution and carbide precipitation associated with quenching and partitioning (Q&P) treatment of medium C steels (0.4 wt% C) alloyed with three levels of silicon (Si) (0.25, 0.75 and 1.5 wt%). Different types of carbides resulting mainly from tempering of martensite (M) and/or partial decomposition of C-enriched austenite have been characterized. The results reveal formation of transition carbides η (Fe2 C) in High (H)-Si (1.5 wt% Si) steel that are stable even at high partitioning temperatures (300 °C). However, these η carbides formed in Medium (M)-Si (0.75 wt% Si) steel were only partially stable, where a fraction of η carbides decomposed to cementite. In Low (L)-Si (0.25 wt% Si) steel, only the presence of cementite precipitates was evident. In addition, the cementite precipitates were found to be relatively coarse in size compared to η carbides, suggesting that cementite grew during the partitioning process at 300 °C. Apart from carbides, segregation of C clusters in M lath boundaries was clearly revealed by APT. In addition, the possible formation of a metastable, hexagonal (ω) phase between the thin nano-twinned high C martensite has been explored.